Nucleotide sequences of the nucleocapsid (NP) and phosphoprotein (P) genes of a Malaysian velogenic Newcastle disease virus strain AF2240 and the production of NP and P proteins in Escherichia coli - Yusoff, Khatijah; Tan , Wen Siang; Kho, Ling Chiew (2006)
The present invention relates to nucleotide sequences encoding the nucleocapsid (NP) protein and phosphoprotein (P) of Newcastle disease virus (NDV) and the production of the corresponding proteins with recombinant plasmids bearing the nucleotide sequences in Escherichia coli